A comprehensive, integrated approach to quality improvement and capacity building in burn care and prevention in low and middle-income countries: An overview - Tom Potokar (Burns, 2020)
Consistent evidence has emerged over many years that the mortality and morbidity outcomes for burn patients in low and middle-income countries (LMICs) lag behind those in more resource rich countries. Interburns is a charity that was set up with the aim of working to reduce the disparity in the number of cases of burns as well as the outcomes for patients in LMICs. This paper provides an overview of a cyclical framework for quality improvement in burn care for use in LMICs that has been developed using an iterative process over the last 10 years. Each phase of the process is outlined together with a description of the tools used to conduct a gap analysis within the service, which is then used to frame a programme of capacity enhancement. Recent externally reviewed projects have demonstrated sustained improvement with the use of this comprehensive and integrated approach over a three-year cycle. This overview paper will be supported by further publications that present these results in detail.